Enabling and Controlling Negative Photoconductance of FePS3 Nanosheets by Hot Carrier Trapping. Issue 10 (11th March 2020) - Ou, Zhenwei; Wang, Ti; Tang, Jibo; Zong, Xinrong; Wang, Wei; Guo, Quanbing; Xu, Yuhao; Zhu, Chao; Wang, Lin; Huang, Wei; Xu, Hongxing
Abstract: 2D materials have aroused tremendous attention in the last decade, and magnetic materials of the 2D scale are rising to prominence in recent years, which may revolutionize current optical and electronic applications. Photoconductivity is a well‐known optical and electrical property, which should be positive as the conductivity of material increases typically upon the absorption of electromagnetic radiation. Here, a controllable switch fromnegative to positive photoconductivity effect of FePS3 nanosheets is enabledby the modulation of the excitation wavelengths. These effects originate from an ultrafast process of hot carrier trapping, as visualized and investigated by the transient absorption microscopy at a quantitative level. This hot carrier trapping process is about 1.25 ps resulting in a lower diffusion constant state (≈3.5 cm 2 s −1 ), which provides deep insight into the intrinsic properties of 2D FePS3 for further study. The results demonstrate experimentally the possibility to tune the electronic properties of 2D magnetic materials by an optical way, which not only induces the change in the magnitude but also in the sign, leading to more understandings and possibilities in 2D optoelectronic devices with many unexpected and multifunctional properties. Abstract : This work reports a controllable positive to negative photoconductance switch of FePS3 nanosheets by hot carrier trapping. The energy of the trapping state and the lifetime of the trapping process have been determined by the wavelength‐dependent photoconductivity and transient absorption microscopy measurements. This finding provides a broad playground to develop more interesting optical properties and functionalities based on 2D FePS3 .